2007
DOI: 10.4321/s0365-66912007000300010
|View full text |Cite
|
Sign up to set email alerts
|

Síndrome de Horner traumático

Abstract: Cervical trauma may damage the sympathetic pathway and result in Horner's syndrome. This may be a manifestation of a life-threatening condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The fracture site was beside the thoracic outlet and relatively close to the lung apex, where the bony fragment, swollen soft tissue, or a hematoma might cause an interruption or compression of the second-order neuron, leading to preganglionic Horner's syndrome (Figure 4). All cases of traumatic Horner's syndrome, or iatrogenic Horner's syndrome, mentioned in the literature are summarized in Table 1 (6)(7)(8)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Karen et al reported osteochondroma of the clavicle, which, although rare, should be considered in the differential diagnosis of causes of Horner's syndrome (10).…”
Section: Discussionmentioning
confidence: 99%
“…The fracture site was beside the thoracic outlet and relatively close to the lung apex, where the bony fragment, swollen soft tissue, or a hematoma might cause an interruption or compression of the second-order neuron, leading to preganglionic Horner's syndrome (Figure 4). All cases of traumatic Horner's syndrome, or iatrogenic Horner's syndrome, mentioned in the literature are summarized in Table 1 (6)(7)(8)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Karen et al reported osteochondroma of the clavicle, which, although rare, should be considered in the differential diagnosis of causes of Horner's syndrome (10).…”
Section: Discussionmentioning
confidence: 99%